PENGARUH SUMBER DAYA MANUSIA DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP KUALITAS LAPORAN KEUANGAN (Studi Pada UKM Yang Terdaftar Pada Dinas Koperasi, Usaha Kecil Dan Menengah Kabupaten Tabalong) - Shinta Avriyanti (Jurnal PubBis, 2018)
This research aims to analyze the influence of human resources, information technology and the quality of financial reports on listed of UKM on the Department of cooperatives, small and medium enterprises Tabalong Regency. Specifically the purpose of the study was to (1) test the influence of human resources to the quality of the financial report of on listed of UKM on the Department of cooperatives, small and medium enterprises Tabalong Regency, (2) to test the influence of information technology to the quality of financial reporting on listed of UKM on the Department of cooperatives, small and medium enterprises Tabalong Regency. This research includes research eksplanatory research. Sampling method with the method of probability sampling. The technique used is the sample the sample random sampling techniques (simple random sampling), namely by means of a lottery. There are 41 respondents in this research. Methods of data analysis using Generalized Structured Component Analysis (GSCA) the results of this study suggest that (1) the human resources impact the quality of the financial statements. (2) information technology does not affect the quality of the financial statements. Keywords: human resources; information technology; quality of financial reports; GSCA.